PANDANGAN POLITIK MAHMOUD AHMADINEJAD STUDI KASUS : HUBUNGAN IRAN-AMERIKA SERIKAT (2005-2009) - Gustri Eni Putri (Dauliyah Journal of Islamic and International Affairs, 2016)
This research is intended to analyze how Ahmadinejad’s political view affects U.S.-Iran relations in 2005-2009 and how such a view has been constructed. This research is also based on the idea that an individual, in this case is the leader, is the factor distinguishing the results of the foreign policies. U.S.-Iran relation, which was getting better, was worsened under Ahmadinejad’s administration. His political decision is resulted from his political view. Indeed, his political view has something to do with the view framing process. The process of framing Ahmadinejad’s political view is closely related to his life and political experiences.